Ocean Alkalinity, Buffering and Biogeochemical Processes. (29th July 2020) - Middelburg, Jack J.; Soetaert, Karline; Hagens, Mathilde
Abstract: Alkalinity, the excess of proton acceptors over donors, plays a major role in ocean chemistry, in buffering and in calcium carbonate precipitation and dissolution. Understanding alkalinity dynamics is pivotal to quantify ocean carbon dioxide uptake during times of global change. Here we review ocean alkalinity and its role in ocean buffering as well as the biogeochemical processes governing alkalinity and pH in the ocean. We show that it is important to distinguish between measurable titration alkalinity and charge balance alkalinity that is used to quantify calcification and carbonate dissolution and needed to understand the impact of biogeochemical processes on components of the carbon dioxide system. A general treatment of ocean buffering and quantification via sensitivity factors is presented and used to link existing buffer and sensitivity factors. The impact of individual biogeochemical processes on ocean alkalinity and pH is discussed and quantified using these sensitivity factors. Processes governing ocean alkalinity on longer time scales such as carbonate compensation, (reversed) silicate weathering, and anaerobic mineralization are discussed and used to derive a close‐to‐balance ocean alkalinity budget for the modern ocean. Plain Language Summary: The ocean plays a major role in the global carbon cycle and the storage of anthropogenic carbon dioxide. This key function of the ocean is related to the reaction of dissolved carbon dioxide with water to form bicarbonate (and minor quantities of carbonic acid and carbonate). Alkalinity, the excess of bases, governs the efficiency at which this occurs and provides buffering capacity toward acidification. Here we discuss ocean alkalinity, buffering, and biogeochemical processes and provide quantitative tools that may help to better understand the role of the ocean in carbon cycling during times of global change. Key Points: Titration and charge balance alkalinity differ The impact of biogeochemical processes on pH depends on environmental conditions Ocean alkalinity budget is balanced when the additional alkalinity input from riverine particulate inorganic carbon and sedimentary sources is included